Preparation method of nano reinforcement assisted graphene reinforced aluminum-based composite material
Through nano-level hard reinforced body assisted ball milling technology, the problem of poor dispersion effect of graphene in aluminum-based composite materials and mismatch of matrix strength is solved, and the high-quality composite of graphene and aluminum is achieved, which improves the strength of the material and Performance, simplifies process and reduces costs.
Patent Information
- Application Number
- CN202411316304.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-20
AI Technical Summary
The dispersion effect of graphene in aluminum-based composite materials is poor, resulting in the mismatch between the matrix strength and the graphene strength, limiting the strengthening effect. High-energy ball milling and other methods are prone to cause graphene defects and reactions, affecting performance.
Using nano-level hard reinforced body assisted ball milling technology, the graphene is more evenly dispersed through long-term uniform dispersion and short-term high-energy ball milling, and the nano-hard reinforced body is introduced into the aluminum matrix grains to inhibit grain growth and defect formation. , realize the preparation of high-quality composite materials.
Improve the dispersion effect and strengthening efficiency of graphene, enhance the dislocation density and work hardening rate of the matrix, realize the high-quality recombination of graphene and aluminum, improve the load transfer effect and the comprehensive performance of the material, simplify the process and reduce the The cost.
Smart Images

Figure CN119194174A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a graphene-reinforced aluminum-based composite material. Background Art
[0002] Graphene is a nanomaterial with high theoretical strength and elastic modulus. According to the composite material strengthening theory, adding a small amount of graphene to the matrix can achieve a good strengthening effect. However, research in recent years has shown that the strengthening effect of single graphene is limited, and the strength limit of graphene-reinforced metal-based composites has reached a certain bottleneck.
[0003] Since graphene is a nanomaterial with high dispersion difficulty, the extremely high surface energy can easily cause agglomeration and pores. In order to evenly disperse graphene, high-energy ball milling and other methods are generally used, which can easily increase graphene defects and reduce intrinsic strength, and also easily cause graphene to react to form Al4C3. On the other hand, many researchers focus their research on graphene / aluminum on the interface between graphene and aluminum, hoping to obtain a strong enough interface to obtain sufficient interface load transfer effect. Graphene generally uses a lower volume fraction and is generally dispersed at the grain boundary, making it difficult to completely disperse to all parts of the matrix. Even if graphene with strong interface bonding is prepared, it can only work in a certain area. When the load is transferred to the matrix, microcracks tend to be generated in the unreinforced matrix, thereby bypassing the graphene and eventually generating macro cracks. Therefore, it is necessary to match the interface strength of graphene with the matrix strength to achieve the best strengthening effect. At present, the method of matrix alloying is generally used to improve the strength of the matrix. However, the introduction of graphene always leads to problems such as the segregation of alloy elements and changes in reaction behavior, resulting in unsatisfactory strengthening effects and even performance degradation.
[0004] Therefore, it is urgent to find a hybrid composite material design that can improve the graphene dispersion effect, increase the matrix strength, and have a synergistic strengthening effect, so as to realize the preparation of nano-reinforcement-assisted graphene aluminum composite materials. Summary of the invention
[0005] In order to solve the problems of poor graphene dispersion effect and mismatch between matrix strength and graphene strength in aluminum-based composite materials, the present invention provides a method for preparing a nano-reinforcement-assisted graphene-reinforced aluminum-based composite material.
[0006] The preparation method of the nano-reinforcement-assisted graphene-reinforced aluminum-based composite material of the present invention is carried out according to the following steps:
[0007] 1. Powder ingredient selection
[0008] Weigh 0.1-4wt.% of graphene, 1-10wt.% of nano-scale hard reinforcement, 0.5-3wt.% of control agent and the remainder of aluminum metal powder as raw materials; weigh an aluminum metal block, the weight ratio of the aluminum metal block to the aluminum metal powder is (3-10):1; the aluminum metal powder and the aluminum metal block are made of the same material; the control agent is stearic acid;
[0009] 2. Dispersion process
[0010] The weighed graphene, nano-scale hard reinforcement, control agent and aluminum metal powder are put into a ball mill, and long-time uniform dispersion ball milling and short-time high-energy ball milling are carried out in sequence. In the high-energy ball milling, the nano-scale hard reinforcement can hit the graphene and make the graphene delaminated and broken, so as to achieve a more uniform dispersion effect. The high-energy ball milling can also make the aluminum metal powder continuously cold welded and broken, so that the nano-scale hard reinforcement enters the grains of the aluminum matrix; after ball milling, the composite material prefabricated powder is obtained by sieving; the control agent plays a role in regulating the energy size of ball milling;
[0011] 3. Preforming of prefabricated powder
[0012] The composite material prefabricated powder is placed in a cold pressing mold for cold pressing to obtain a graphene-nanoscale hard reinforcement-aluminum prefabricated body; the mold is placed in a heating furnace, filled with nitrogen and heated at 600°C to allow the control agent to fully react and volatilize;
[0013] 4. Aluminum Metal Infiltration
[0014] The aluminum metal block weighed in step 1 is placed in a graphite mold at the bottom of the furnace chamber of the infiltration furnace, and the graphene-nanoscale hard reinforcement-aluminum preform obtained in step 3 is placed in the upper part of the furnace chamber of the infiltration furnace, and the vacuum infiltration furnace is heated to heat the preform to 560-650°C at 3-10°C / min, and the preform is kept warm for 0.5-3h; the aluminum metal block weighed in step 1 is heated to 780-880°C and kept warm for 0.5-2h to obtain molten aluminum metal; the preheated graphene-nanoscale hard reinforcement-aluminum preform is immersed in the molten aluminum metal and the heating is stopped, and a high-density nano-reinforcement-assisted graphene-reinforced aluminum-based composite ingot is obtained after natural cooling;
[0015] 5. Large plastic deformation treatment and composition homogenization
[0016] The highly dense nano-reinforcement-assisted graphene-reinforced aluminum-based composite material ingot obtained in step 4 is subjected to large plastic deformation treatment and component homogenization treatment in sequence to obtain a nano-scale hard reinforcement-assisted graphene-reinforced aluminum-based composite material.
[0017] Principle and beneficial effects of the present invention:
[0018] 1. The present invention introduces a second hard nano-reinforcement body during the ball milling process of graphene and aluminum powder, which is equivalent to a nano-scale grinding ball during the ball milling process. The graphene sheets are continuously collided during the ball milling process, and the effect of breaking, thinning and dispersing graphene is far superior to that of conventional millimeter-scale ball milling balls, thereby achieving high-quality dispersion of graphene and improving the strengthening efficiency of graphene.
[0019] 2. The nano-scale hard reinforcement introduced in the present invention can enhance the friction between the grinding ball and the aluminum powder, thereby increasing the ball milling energy. The general powder metallurgy method seeks to disperse the reinforcement on the surface of the aluminum powder. Due to the larger ball milling energy, the present invention allows the aluminum powder to be continuously cold welded and crushed, which is more conducive to achieving the entry of graphene and nano-hard reinforcement into the interior of the aluminum powder and even the interior of the aluminum grains, increasing the range in which the reinforcement can be dispersed to a certain extent, and greatly improving the dispersion effect.
[0020] 3. The present invention introduces nano-hard reinforcements into the matrix grains to play an additional second phase strengthening role in the matrix. Dislocations encounter graphene during the slip process. Due to the layered structure of graphene, dislocations are easily absorbed. When encountering hard nano-reinforcements, they can only slip through a bypass mechanism. Therefore, the introduction of hard nano-reinforcements in the present invention increases the dislocation density of the matrix and improves the work hardening rate.
[0021] 4. The present invention introduces nano-hard reinforcements to inhibit grain growth during heat treatment. Generally, when the temperature of the heat-treatable matrix aluminum alloy during solution treatment is higher than 500°C, the grains will grow rapidly at this temperature. The present invention introduces additional nano-reinforcements to pin the grain boundaries, inhibit the growth of the grains, and obtain a stronger fine grain strengthening effect.
[0022] 5. In the composite material prepared by the present invention, the defects of graphene are controllable and do not react with aluminum. Through the regulation of the ball milling process, no excessive defects are introduced, the graphene structure is complete and it is not easy to react with aluminum to form harmful intermetallic compounds, thus achieving high-quality composite of graphene and aluminum. A good interface and a stronger matrix achieve a further breakthrough in the load transfer effect.
[0023] 6. The nano-reinforcement-assisted graphene-reinforced aluminum-based composite material prepared by the present invention realizes the coordination of zero-dimensional and two-dimensional, deformable and rigid reinforcements. The zero-dimensional rigid reinforcement causes dislocations to multiply during deformation, and the two-dimensional deformable graphene absorbs dislocations to coordinate matrix deformation, thereby achieving a comprehensive improvement in strength and plasticity and obtaining a synergistic effect. In addition, the preparation process is simple, the parameters are controllable, the cost is low, and the performance is excellent, which is a breakthrough compared to the current graphene / aluminum preparation process. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a microscopic photograph of the composite material prefabricated powder obtained in Example 1;
[0025] Figure 2 This is the Raman image of the nano-reinforcement assisted graphene reinforced aluminum-based composite material obtained in Example 1;
[0026] Figure 3 This is the metallographic microstructure diagram of the nano-reinforcement assisted graphene reinforced aluminum-based composite material obtained in Example 1. DETAILED DESCRIPTION
[0027] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any reasonable combination of the specific implementation modes.
[0028] Specific implementation method 1: The preparation method of the nano-reinforcement-assisted graphene-reinforced aluminum-based composite material in this implementation method is carried out according to the following steps:
[0029] 1. Powder ingredient selection
[0030] Weigh 0.1-4wt.% of graphene, 1-10wt.% of nano-scale hard reinforcement, 0.5-3wt.% of control agent and the remainder of aluminum metal powder as raw materials; weigh an aluminum metal block, the weight ratio of the aluminum metal block to the aluminum metal powder is (3-10):1; the aluminum metal powder and the aluminum metal block are made of the same material; the control agent is stearic acid;
[0031] 2. Dispersion process
[0032] The weighed graphene, nano-scale hard reinforcement, control agent and aluminum metal powder are put into a ball mill, and long-time uniform dispersion ball milling and short-time high-energy ball milling are carried out in sequence. In the high-energy ball milling, the nano-scale hard reinforcement can hit the graphene and make the graphene delaminated and broken to achieve a more uniform dispersion effect. The high-energy ball milling can also make the aluminum metal powder continuously cold welded and broken, so that the nano-scale hard reinforcement enters the grains of the aluminum matrix; after ball milling, it is sieved to obtain a composite material prefabricated powder;
[0033] 3. Preforming of prefabricated powder
[0034] The composite material prefabricated powder is placed in a cold pressing mold for cold pressing to obtain a graphene-nanoscale hard reinforcement-aluminum prefabricated body; the mold is placed in a heating furnace, filled with nitrogen and heated at 600°C to allow the control agent to fully react and volatilize;
[0035] 4. Aluminum Metal Infiltration
[0036] The aluminum metal block weighed in step 1 is placed in a graphite mold at the bottom of the furnace chamber of the infiltration furnace, and the graphene-nanoscale hard reinforcement-aluminum preform obtained in step 3 is placed in the upper part of the furnace chamber of the infiltration furnace, and the vacuum infiltration furnace is heated to heat the preform to 560-650°C at 3-10°C / min, and the preform is kept warm for 0.5-3h; the aluminum metal block weighed in step 1 is heated to 780-880°C and kept warm for 0.5-2h to obtain molten aluminum metal; the preheated graphene-nanoscale hard reinforcement-aluminum preform is immersed in the molten aluminum metal and the heating is stopped, and a high-density nano-reinforcement-assisted graphene-reinforced aluminum-based composite ingot is obtained after natural cooling;
[0037] 5. Large plastic deformation treatment and composition homogenization
[0038] The highly dense nano-reinforcement-assisted graphene-reinforced aluminum-based composite material ingot obtained in step 4 is subjected to large plastic deformation treatment and component homogenization treatment in sequence to obtain a nano-scale hard reinforcement-assisted graphene-reinforced aluminum-based composite material.
[0039] This embodiment has the following beneficial effects:
[0040] 1. This embodiment introduces a second hard nano-reinforcement body during the ball milling process of graphene and aluminum powder, which is equivalent to a nano-scale grinding ball during the ball milling process. The graphene sheets are continuously collided during the ball milling process, and the effect of breaking, thinning and dispersing the graphene is far superior to that of conventional millimeter-scale ball milling balls, thereby achieving high-quality dispersion of graphene and improving the strengthening efficiency of graphene.
[0041] 2. The nano-scale hard reinforcement introduced in this embodiment can enhance the friction between the grinding ball and the aluminum powder, and increase the ball milling energy. The general powder metallurgy method seeks to disperse the reinforcement on the surface of the aluminum powder. Due to the large ball milling energy, this embodiment makes the aluminum powder cold welding-crushing cycle continuously, which is more conducive to achieving the graphene and nano-hard reinforcement entering the aluminum powder and even the aluminum grains, which increases the range of the reinforcement to a certain extent and greatly improves the dispersion effect.
[0042] 3. This embodiment introduces nano-hard reinforcements into the matrix grains to play an additional second phase strengthening role in the matrix. Dislocations encounter graphene during the slip process. Due to the layered structure of graphene, dislocations are easily absorbed. When encountering hard nano-reinforcements, they can only slip through a bypass mechanism. Therefore, the introduction of hard nano-reinforcements in this embodiment increases the dislocation density of the matrix and improves the work hardening rate.
[0043] 4. This embodiment introduces nano-hard reinforcements to inhibit grain growth during heat treatment. Generally, when the temperature of the heat-treatable matrix aluminum alloy during solution treatment is higher than 500°C, the grains will grow rapidly at this temperature. This embodiment introduces additional nano-reinforcements to pin the grain boundaries, inhibit the growth of the grains, and obtain a stronger fine grain strengthening effect.
[0044] 5. In the composite material prepared in this embodiment, the defects of graphene are controllable and do not react with aluminum. Through the regulation of the ball milling process, no excessive defects are introduced, and the graphene structure is complete and not easy to react with aluminum to form harmful intermetallic compounds, thus achieving high-quality composite of graphene and aluminum. A good interface and a stronger matrix achieve a further breakthrough in the load transfer effect.
[0045] 6. The nano-reinforcement-assisted graphene-reinforced aluminum-based composite material prepared in this embodiment realizes the coordination of zero-dimensional and two-dimensional, deformable and rigid reinforcements. The zero-dimensional rigid reinforcement causes dislocations to multiply during deformation, and the two-dimensional deformable graphene absorbs dislocations to coordinate matrix deformation, thereby achieving a comprehensive improvement in strength and plasticity and obtaining a synergistic effect. In addition, the preparation process is simple, the parameters are controllable, the cost is low, and the performance is excellent, which is a breakthrough compared to the current graphene / aluminum preparation process.
[0046] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that: the graphene described in step 1 is few-layer graphene with an average sheet diameter of 100nm to 10μm and an average thickness of 0.3 to 20nm.
[0047] Specific implementation method three: This implementation method is different from specific implementation methods one or two in that: the nano-scale hard reinforcement in step one is nano-boron carbide, nano-titanium carbide, nano-aluminum oxide, nano-silicon oxide, nano-silicon nitride or nano-silicon carbide, and the average particle size is 10 to 1000 nm.
[0048] Specific embodiment four: This embodiment differs from any of specific embodiments one to three in that: the aluminum metal described in step one is one of Al-Si alloy, Al-Cu alloy, Al-Mg alloy, Al-Si-Cu alloy, Al-Si-Mg alloy, Al-Cu-Mg alloy, Al-Zn-Cu alloy, Al-Zn-Mg-Cu alloy, Al-Be alloy, Al-Li alloy, Al-Si-Cu-Mg alloy, or a combination of several of them. The mass fraction of Si in the Al-Si alloy is 0.5% to 25%; the mass fraction of Cu in the Al-Cu alloy is 0.5% to 53%; the mass fraction of Mg in the Al-Mg alloy is 0.5% to 38%; the mass fraction of Si in the Al-Si-Cu alloy is 0.5% to 25%, and the mass fraction of Cu is 0.5% to 53%; the mass fraction of Si in the Al-Si-Mg alloy is 0.5% to 25%, and the mass fraction of Mg is 0.5% to 38%; the mass fraction of Cu in the Al-Cu-Mg alloy is 0.5% to 53%, and the mass fraction of Mg is 0.5% to 38%; Al-Z The mass fraction of Zn in the n-Cu alloy is 0.5% to 55%, and the mass fraction of Cu is 0.5% to 53%; the mass fraction of Zn in the Al-Zn-Mg-Cu alloy is 0.5% to 55%, the mass fraction of Mg is 0.5% to 38%, and the mass fraction of Cu is 0.5% to 53%; the mass fraction of Be in the Al-Be alloy is 0.5% to 20%; the mass fraction of Li in the Al-Li alloy is 0.5% to 35%; the mass fraction of Si in the Al-Si-Cu-Mg alloy is 0.5% to 25%, the mass fraction of Cu is 0.5% to 53%, and the mass fraction of Mg is 0.5% to 38%.
[0049] Specific implementation method 5: This implementation method is different from specific implementation methods 1 to 4 in that:
[0050] The process of long-term uniform dispersion ball milling in step 2 is: the ball milling speed is 50-150 rpm, and the ball milling time is 3-18 hours;
[0051] The process of short-time high-energy ball milling in step 2 is as follows: the ball milling speed is 150-300 rpm, and the ball milling time is 1-6 hours.
[0052] Specific embodiment 6: This embodiment is different from any one of specific embodiments 1 to 5 in that: the cold pressing process described in step 3 is: pressurizing the mixed powder to 5 to 15 MPa at a pressing speed of 0.1 to 10 mm / min and maintaining the pressure for 10 to 30 minutes.
[0053] Specific embodiment 7: This embodiment is different from any one of specific embodiments 1 to 6 in that the atmosphere in the impregnation furnace used in step 4 is one of vacuum, nitrogen atmosphere, and air atmosphere.
[0054] Specific implementation eight: This implementation differs from any one of specific implementations one to seven in that: the large plastic deformation process described in step five is an extrusion, rolling, or forging deformation process.
[0055] Specific embodiment 9: This embodiment is different from specific embodiment 8 in that the temperature of the extrusion deformation treatment or rolling treatment is 400°C to 500°C, and the deformation ratio is (7 to 50):1.
[0056] Specific embodiment ten: This embodiment differs from any one of specific embodiments one to nine in that: the temperature of the component homogenization treatment in step five is 450° C. to 550° C., and the time is 1 to 6 hours.
[0057] Example 1
[0058] The preparation method of the nano-reinforcement-assisted graphene-reinforced aluminum-based composite material of this embodiment is carried out according to the following steps:
[0059] 1. Powder ingredient selection
[0060] Weigh 1wt.% of graphene, 10wt.% of nano-scale hard reinforcement, 1wt.% of control agent and the remainder of aluminum metal powder as raw materials; weigh an aluminum metal block, the weight ratio of the aluminum metal block to the aluminum metal powder is 5:1; the aluminum metal powder and the aluminum metal block are made of the same material; the control agent is stearic acid;
[0061] The graphene in step 1 is a few-layer graphene with an average sheet diameter of 1 μm and an average thickness of 5 nm;
[0062] The nano-scale hard reinforcement in step 1 is nano-silicon carbide with an average particle size of 150nm;
[0063] The aluminum metal in step 1 is 6061Al metal, and the average particle size of the aluminum metal powder is 10 μm;
[0064] 2. Dispersion process
[0065] The weighed graphene, nano-scale hard reinforcement, control agent and aluminum metal powder are put into a ball mill, and long-time uniform dispersion ball milling and short-time high-energy ball milling are carried out in sequence. In the high-energy ball milling, the nano-scale hard reinforcement can hit the graphene and make the graphene delaminated and broken to achieve a more uniform dispersion effect. The high-energy ball milling can also make the aluminum metal powder continuously cold welded and broken, so that the nano-scale hard reinforcement enters the grains of the aluminum matrix; after ball milling, it is sieved to obtain a composite material prefabricated powder;
[0066] The process of long-term uniform dispersion ball milling in step 2 is: the ball milling speed is 100 rpm and the ball milling time is 6 hours; the process of short-term high-energy ball milling in step 2 is: the ball milling speed is 250 rpm and the ball milling time is 2 hours.
[0067] 3. Preforming of prefabricated powder
[0068] The composite material prefabricated powder is placed in a cold pressing mold for cold pressing to obtain a graphene-nanoscale hard reinforcement-aluminum prefabricated body; the mold is placed in a heating furnace, filled with nitrogen, and heated to 600°C at 5°C / min and kept at this temperature for 4 hours to allow the control agent to fully react and volatilize;
[0069] The cold pressing process in step 3 is as follows: pressurizing the mixed powder to 10 MPa at a pressurizing speed of 2 mm / min and maintaining the pressure for 10 minutes;
[0070] 4. Aluminum Metal Infiltration
[0071] The aluminum metal block weighed in step 1 is placed in a graphite mold at the bottom of the furnace chamber of the infiltration furnace, and the graphene-nanoscale hard reinforcement-aluminum preform obtained in step 3 is placed in the upper part of the furnace chamber of the infiltration furnace, and the vacuum infiltration furnace is heated to heat the preform to 600°C at 5°C / min, and the preform is kept warm for 3 hours; the aluminum metal block weighed in step 1 is heated to 800°C and kept warm for 1 hour to obtain molten aluminum metal; the preheated graphene-nanoscale hard reinforcement-aluminum preform is immersed in the molten aluminum metal and the heating is stopped, and a high-density nano-reinforcement-assisted graphene-reinforced aluminum-based composite material ingot is obtained after natural cooling;
[0072] The atmosphere in the impregnation furnace used in step 4 is a nitrogen atmosphere;
[0073] 5. Large plastic deformation treatment and composition homogenization
[0074] The highly dense nano-reinforcement-assisted graphene-reinforced aluminum-based composite material ingot obtained in step 4 is subjected to large plastic deformation treatment and component homogenization treatment in sequence to obtain a nano-scale hard reinforcement-assisted graphene-reinforced aluminum-based composite material.
[0075] The large plastic deformation treatment in step 5 is extrusion, the temperature is 480°C, and the deformation ratio is 10:1;
[0076] The temperature of the component homogenization treatment in step 5 is 540° C. and the time is 4 hours;
[0077] Figure 1This is a micrograph of the composite material preform powder obtained in Example 1; it can be seen from the figure that the aluminum powder presents a slight cold welding state, but is much smaller than the original particle size, indicating that repeated cold welding-crushing cycles of the aluminum powder are achieved, which is beneficial to the dispersion of the reinforcement in the matrix; the diameter and thickness of the graphene sheets in the field of view are greatly reduced, proving the beneficial effect of nano-silicon carbide on dispersion, and the nano-silicon carbide itself is also relatively uniformly dispersed. Figure 2 This is the Raman image of the nano-reinforcement assisted graphene reinforced aluminum-based composite material obtained in Example 1; it can be seen from the figure that the defects of graphene are still within a reasonable range, and no excessive defects are generated due to the increase in ball milling energy, which will not lead to the production of Al4C3. Figure 3 The metallographic microstructure diagram of the nano-reinforcement assisted graphene reinforced aluminum-based composite material obtained in Example 1. It can be seen that the composite material has almost no holes and agglomerations, the reinforcement is evenly dispersed, and the composite material has a high density. In the nano-reinforcement assisted graphene reinforced aluminum-based composite material, the graphene is broken, thinned and dispersed, the dispersion of the two in the matrix grains is improved, the dispersion efficiency is improved, and there is no excessive defect induction Al4C3 production; the coordination of zero-dimensional and two-dimensional, variable and rigid reinforcements is achieved, the zero-dimensional rigid reinforcement multiplies dislocations during deformation, and the two-dimensional variable graphene absorbs dislocations to coordinate matrix deformation, achieving a comprehensive improvement in strength and plasticity; on the other hand, the nano-reinforcement helps graphene suppress the grain growth behavior of homogenization treatment (above 500°C), and improves the fine grain strengthening effect. The present invention solves the problem that the strength of graphene in the graphene / Al composite material system does not match the strength of the matrix, resulting in cracks that are easy to expand in the matrix. Taking 6061Al as an example, nano-silicon carbide reinforcement increases the strength of the matrix by more than two times, improves the matching degree between the strength of the reinforcement and the matrix, and prevents the matrix from generating microcracks in advance during the stress transfer process, and the transmission of microcracks in the matrix is also suppressed. The combination of the two reinforcements achieves a synergistic effect. The nano-reinforcement-assisted graphene-enhanced aluminum-based composite material prepared in this embodiment has an elastic modulus of 96GPa, a yield strength of 482MPa, a tensile strength of 555MPa, and an elongation of 10.4%.
[0078] Embodiment 2:
[0079] The preparation method of the nano-reinforcement-assisted graphene-reinforced aluminum-based composite material of this embodiment is carried out according to the following steps:
[0080] 1. Powder ingredient selection
[0081] Weigh 1wt.% of graphene, 5wt.% of nano-scale hard reinforcement, 1wt.% of control agent and the remainder of aluminum metal powder as raw materials; weigh an aluminum metal block, the weight ratio of the aluminum metal block to the aluminum metal powder is 5:1; the aluminum metal powder and the aluminum metal block are made of the same material; the control agent is stearic acid;
[0082] The graphene in step 1 is a few-layer graphene with an average sheet diameter of 1 μm and an average thickness of 5 nm;
[0083] The nano-scale hard reinforcement in step 1 is nano-silicon carbide with an average particle size of 150nm;
[0084] The aluminum metal in step 1 is 6061Al metal, and the average particle size of the aluminum metal powder is 10 μm;
[0085] 2. Dispersion process
[0086] The weighed graphene, nano-scale hard reinforcement, control agent and aluminum metal powder are put into a ball mill, and long-time uniform dispersion ball milling and short-time high-energy ball milling are carried out in sequence. In the high-energy ball milling, the nano-scale hard reinforcement can hit the graphene and make the graphene delaminated and broken to achieve a more uniform dispersion effect. The high-energy ball milling can also make the aluminum metal powder continuously cold welded and broken, so that the nano-scale hard reinforcement enters the grains of the aluminum matrix; after ball milling, it is sieved to obtain a composite material prefabricated powder;
[0087] The process of long-term uniform dispersion ball milling in step 2 is: the ball milling speed is 100 rpm and the ball milling time is 6 hours; the process of short-term high-energy ball milling in step 2 is: the ball milling speed is 250 rpm and the ball milling time is 2 hours.
[0088] 3. Preforming of prefabricated powder
[0089] The composite material prefabricated powder is placed in a cold pressing mold for cold pressing to obtain a graphene-nanoscale hard reinforcement-aluminum prefabricated body; the mold is placed in a heating furnace, filled with nitrogen, and heated to 600°C at 5°C / min and kept at this temperature for 4 hours to allow the control agent to fully react and volatilize;
[0090] The cold pressing process in step 3 is as follows: pressurizing the mixed powder to 10 MPa at a pressurizing speed of 2 mm / min and maintaining the pressure for 10 minutes;
[0091] 4. Aluminum Metal Infiltration
[0092] The aluminum metal block weighed in step 1 is placed in a graphite mold at the bottom of the furnace chamber of the infiltration furnace, and the graphene-nanoscale hard reinforcement-aluminum preform obtained in step 3 is placed in the upper part of the furnace chamber of the infiltration furnace, and the vacuum infiltration furnace is heated to heat the preform to 600°C at 5°C / min, and the preform is kept warm for 3 hours; the aluminum metal block weighed in step 1 is heated to 800°C and kept warm for 1 hour to obtain molten aluminum metal; the preheated graphene-nanoscale hard reinforcement-aluminum preform is immersed in the molten aluminum metal and the heating is stopped, and a high-density nano-reinforcement-assisted graphene-reinforced aluminum-based composite material ingot is obtained after natural cooling;
[0093] The atmosphere in the impregnation furnace used in step 4 is a nitrogen atmosphere;
[0094] 5. Large plastic deformation treatment and composition homogenization
[0095] The highly dense nano-reinforcement-assisted graphene-reinforced aluminum-based composite material ingot obtained in step 4 is subjected to large plastic deformation treatment and component homogenization treatment in sequence to obtain a nano-scale hard reinforcement-assisted graphene-reinforced aluminum-based composite material.
[0096] The large plastic deformation treatment in step 5 is extrusion, the temperature is 480°C, and the deformation ratio is 10:1;
[0097] The temperature of the component homogenization treatment in step 5 is 540° C. and the time is 4 hours;
[0098] The nano-reinforcement-assisted graphene-reinforced aluminum-based composite material prepared in Example 2 has an elastic modulus of 87 GPa, a yield strength of 423 MPa, a tensile strength of 492 MPa, and an elongation of 16.7%.
[0099] Embodiment 3:
[0100] The preparation method of the nano-reinforcement-assisted graphene-reinforced aluminum-based composite material of this embodiment is carried out according to the following steps:
[0101] 1. Powder ingredient selection
[0102] Weigh 1wt.% of graphene, 2wt.% of nano-scale hard reinforcement, 1wt.% of control agent and the remainder of aluminum metal powder as raw materials; weigh an aluminum metal block, the weight ratio of the aluminum metal block to the aluminum metal powder is 5:1; the aluminum metal powder and the aluminum metal block are made of the same material; the control agent is stearic acid;
[0103] The graphene in step 1 is a few-layer graphene with an average sheet diameter of 1 μm and an average thickness of 5 nm;
[0104] The nano-scale hard reinforcement in step 1 is nano-silicon carbide with an average particle size of 150nm;
[0105] The aluminum metal in step 1 is 6061Al metal, and the average particle size of the aluminum metal powder is 10 μm;
[0106] 2. Dispersion process
[0107] The weighed graphene, nano-scale hard reinforcement, control agent and aluminum metal powder are put into a ball mill, and long-time uniform dispersion ball milling and short-time high-energy ball milling are carried out in sequence. In the high-energy ball milling, the nano-scale hard reinforcement can hit the graphene and make the graphene delaminated and broken to achieve a more uniform dispersion effect. The high-energy ball milling can also make the aluminum metal powder continuously cold welded and broken, so that the nano-scale hard reinforcement enters the grains of the aluminum matrix; after ball milling, it is sieved to obtain a composite material prefabricated powder;
[0108] The process of long-term uniform dispersion ball milling in step 2 is: the ball milling speed is 100 rpm and the ball milling time is 6 hours; the process of short-term high-energy ball milling in step 2 is: the ball milling speed is 250 rpm and the ball milling time is 2 hours.
[0109] 3. Preforming of prefabricated powder
[0110] The composite material prefabricated powder is placed in a cold pressing mold for cold pressing to obtain a graphene-nanoscale hard reinforcement-aluminum prefabricated body; the mold is placed in a heating furnace, filled with nitrogen, and heated to 600°C at 5°C / min and kept at this temperature for 4 hours to allow the control agent to fully react and volatilize;
[0111] The cold pressing process in step 3 is as follows: pressurizing the mixed powder to 10 MPa at a pressurizing speed of 2 mm / min and maintaining the pressure for 10 minutes;
[0112] 4. Aluminum Metal Infiltration
[0113] The aluminum metal block weighed in step 1 is placed in a graphite mold at the bottom of the furnace chamber of the infiltration furnace, and the graphene-nanoscale hard reinforcement-aluminum preform obtained in step 3 is placed in the upper part of the furnace chamber of the infiltration furnace, and the vacuum infiltration furnace is heated to heat the preform to 600°C at 5°C / min, and the preform is kept warm for 3 hours; the aluminum metal block weighed in step 1 is heated to 800°C and kept warm for 1 hour to obtain molten aluminum metal; the preheated graphene-nanoscale hard reinforcement-aluminum preform is immersed in the molten aluminum metal and the heating is stopped, and a high-density nano-reinforcement-assisted graphene-reinforced aluminum-based composite material ingot is obtained after natural cooling;
[0114] The atmosphere in the impregnation furnace used in step 4 is a nitrogen atmosphere;
[0115] 5. Large plastic deformation treatment and composition homogenization
[0116] The highly dense nano-reinforcement-assisted graphene-reinforced aluminum-based composite material ingot obtained in step 4 is subjected to large plastic deformation treatment and component homogenization treatment in sequence to obtain a nano-scale hard reinforcement-assisted graphene-reinforced aluminum-based composite material.
[0117] The large plastic deformation treatment in step 5 is extrusion, the temperature is 480°C, and the deformation ratio is 10:1;
[0118] The temperature of the component homogenization treatment in step 5 is 540°C and the time is 4 hours;
[0119] The nano-reinforcement-assisted graphene-reinforced aluminum-based composite material prepared in Example 3 has an elastic modulus of 101 GPa, a yield strength of 511 MPa, a tensile strength of 597 MPa, and an elongation of 6.5%.
Claims
1. A method for preparing a nano-reinforcement-assisted graphene-reinforced aluminum-based composite material, characterized in that: The preparation method of the nano-reinforcement-assisted graphene-reinforced aluminum-based composite material is carried out according to the following steps:
1. Powder ingredient selection Weigh 0.1-4wt.% of graphene, 1-10wt.% of nano-scale hard reinforcement, 0.5-3wt.% of control agent and the balance of aluminum metal powder as raw materials; weigh an aluminum metal block, the weight ratio of the aluminum metal block to the aluminum metal powder is (3-10):1; the aluminum metal powder and the aluminum metal block are made of the same material; The control agent is stearic acid; 2. Dispersion process The weighed graphene, nano-scale hard reinforcement, control agent and aluminum metal powder are put into a ball mill, and long-time uniform dispersion ball milling and short-time high-energy ball milling are carried out in sequence. In the high-energy ball milling, the nano-scale hard reinforcement can hit the graphene and make the graphene delaminated and broken to achieve a more uniform dispersion effect. The high-energy ball milling can also make the aluminum metal powder continuously cold welded and broken, so that the nano-scale hard reinforcement enters the grains of the aluminum matrix; after ball milling, it is sieved to obtain a composite material prefabricated powder; 3. Preforming of prefabricated powder The composite material prefabricated powder is placed in a cold pressing mold for cold pressing to obtain a graphene-nanoscale hard reinforcement-aluminum prefabricated body; the mold is placed in a heating furnace, filled with nitrogen and heated at 600°C to allow the control agent to fully react and volatilize; 4. Aluminum Metal Infiltration The aluminum metal block weighed in step 1 is placed in a graphite mold at the bottom of the furnace chamber of the infiltration furnace, and the graphene-nanoscale hard reinforcement-aluminum preform obtained in step 3 is placed in the upper part of the furnace chamber of the infiltration furnace, and the vacuum infiltration furnace is heated to heat the preform to 560-650°C at 3-10°C / min, and the preform is kept warm for 0.5-3h; the aluminum metal block weighed in step 1 is heated to 780-880°C and kept warm for 0.5-2h to obtain molten aluminum metal; the preheated graphene-nanoscale hard reinforcement-aluminum preform is immersed in the molten aluminum metal and the heating is stopped, and a high-density nano-reinforcement-assisted graphene-reinforced aluminum-based composite ingot is obtained after natural cooling; 5. Large plastic deformation treatment and composition homogenization The highly dense nano-reinforcement-assisted graphene-reinforced aluminum-based composite material ingot obtained in step 4 is subjected to large plastic deformation treatment and component homogenization treatment in sequence to obtain a nano-scale hard reinforcement-assisted graphene-reinforced aluminum-based composite material.
2. The method for preparing a nano-reinforcement-assisted graphene-reinforced aluminum-based composite material according to claim 1, characterized in that: The graphene in step 1 is a few-layer graphene with an average sheet diameter of 100nm to 10μm and an average thickness of 0.3 to 20nm.
3. The method for preparing a nano-reinforcement-assisted graphene-reinforced aluminum-based composite material according to claim 1, characterized in that: The nano-scale hard reinforcement in step 1 is nano-boron carbide, nano-titanium carbide, nano-aluminum oxide, nano-silicon oxide, nano-silicon nitride or nano-silicon carbide, and the average particle size is 10 to 1000 nm.
4. The method for preparing a nano-reinforcement-assisted graphene-reinforced aluminum-based composite material according to claim 1, characterized in that: The aluminum metal in step 1 is one of Al-Si alloy, Al-Cu alloy, Al-Mg alloy, Al-Si-Cu alloy, Al-Si-Mg alloy, Al-Cu-Mg alloy, Al-Zn-Cu alloy, Al-Zn-Mg-Cu alloy, Al-Be alloy, Al-Li alloy, Al-Si-Cu-Mg alloy, or a combination of several thereof; The mass fraction of Si in the Al-Si alloy is 0.5% to 25%; The mass fraction of Cu in the Al-Cu alloy is 0.5% to 53%; The mass fraction of Mg in the Al-Mg alloy is 0.5% to 38%; The mass fraction of Si in Al-Si-Cu alloy is 0.5% to 25%, and the mass fraction of Cu is 0.5% to 53%; The mass fraction of Si in Al-Si-Mg alloy is 0.5% to 25%, and the mass fraction of Mg is 0.5% to 38%; The mass fraction of Cu in Al-Cu-Mg alloy is 0.5% to 53%, and the mass fraction of Mg is 0.5% to 38%; The mass fraction of Zn in Al-Zn-Cu alloy is 0.5% to 55%, and the mass fraction of Cu is 0.5% to 53%; The mass fraction of Zn in Al-Zn-Mg-Cu alloy is 0.5% to 55%, the mass fraction of Mg is 0.5% to 38%, and the mass fraction of Cu is 0.5% to 53%; The mass fraction of Be in Al-Be alloy is 0.5% to 20%; The mass fraction of Li in Al-Li alloy is 0.5% to 35%; The mass fraction of Si in the Al-Si-Cu-Mg alloy is 0.5% to 25%, the mass fraction of Cu is 0.5% to 53%, and the mass fraction of Mg is 0.5% to 38%.
5. The method for preparing a nano-reinforcement-assisted graphene-reinforced aluminum-based composite material according to claim 1, characterized in that: The process of long-term uniform dispersion ball milling in step 2 is: the ball milling speed is 50-150 rpm, and the ball milling time is 3-18 hours; The process of short-time high-energy ball milling in step 2 is as follows: the ball milling speed is 150-300 rpm, and the ball milling time is 1-6 hours.
6. The method for preparing a nano-reinforcement-assisted graphene-reinforced aluminum-based composite material according to claim 1, characterized in that: The cold pressing process in step 3 is as follows: pressurizing the mixed powder to 5-15 MPa at a pressurizing speed of 0.1-10 mm / min and maintaining the pressure for 10-30 minutes.
7. The method for preparing a nano-reinforcement-assisted graphene-reinforced aluminum-based composite material according to claim 1, characterized in that: The atmosphere in the impregnation furnace used in step 4 is one of vacuum, nitrogen and air.
8. The method for preparing a nano-reinforcement-assisted graphene-reinforced aluminum-based composite material according to claim 1, characterized in that: The large plastic deformation process described in step 5 is extrusion, rolling, and forging deformation process.
9. The method for preparing a nano-reinforcement-assisted graphene-reinforced aluminum-based composite material according to claim 8, characterized in that: The temperature of the extrusion deformation treatment or rolling treatment is 400° C. to 500° C., and the deformation ratio is (7 to 50):
1.
10. The method for preparing a nano-reinforcement-assisted graphene-reinforced aluminum-based composite material according to claim 1, characterized in that: In step 5, the temperature for the component homogenization treatment is 450° C. to 550° C., and the time is 1 to 6 hours.
Citation Information
Patent Citations
Method for preparing graphene enhanced aluminum alloy composite material
CN109234658A
Preparation method of graphene-silicon nitride synergistically reinforced aluminum-based composite material
CN116037930A
Carbon nano-reinforced aluminum-based conductor material and preparation method
US20210172043A1
Process and composition for formation of hybrid aluminum composite coating
US20210316398A1
Graphene-reinforced magnesium-based composite material, preparation method for same, and applications thereof
WO2022057232A1
